Forty hadith on riba - Ali, Mohammed Farid (Dar al Wahi Publication, 2019)
This collection of forty hadith on riba deliberates the danger and prohibition of ribÉ, description and types of riba, and business transactions that resemble riba. Malaysia champions Islamic banking and finance in the market, and academic institutions that offer the best Islamic banking and finance programs. The whole objective of Islamic financing is to free trades and transactions from riba. Without deliverance from ribÉ, justice is not attainable in the socio-economic life of people. This forty hadith collection serves as the primary reference source for those embarking on new business venture and commencing studies on Islamic finance.